EMERGENCY NON-OBSTETRIC SURGERY DURING PREGNANCY: ANESTHETIC AND PAIN MANAGEMENT IN OVARIAN CYST TORSION - Leonardo, Peter; Anggraeni, Novita; Masjkur, Diana (Faculty of Medicine Universitas Kristen Duta Wacana, 2024)
The management of non-obstetric emergency surgeries during pregnancy presents unique challenges that necessitate careful consideration of both maternal and fetal health. This case report outlines the management of a pregnant patient (G3P2A0H2, 10-11 weeks gestation) who presented with acute abdominal pain due to a suspected ovarian cyst torsion. The patient underwent exploratory laparotomy under spinal anesthesia with bupivacaine, morphine, and fentanyl. Postoperative pain was managed using a multimodal analgesic strategy including surgical wound infiltration with 0.25% ropivacaine combined with dexamethasone. This technique was used to minimize opioid use and enhance recovery. The patient experienced stable hemodynamics and minimal postoperative pain (VAS 1-2), and was discharged on the third postoperative day. This case highlights the importance of effective pain management, particularly during non-obstetric surgeries during pregnancy. Regional anesthesia, along with local infiltration of ropivacaine and dexamethasone, provides an effective pain control strategy, contributing to faster recovery and enhanced patient satisfaction while minimizing systemic opioid exposure.